VSCT algorithm for graph partitioning based on volume, size, cuts and time. Issue 3 (4th May 2023) - Sakouhi, Chayma; Khaldi, Abir; Ben Ghezala, Henda
Abstract : Dealing with large-scale graphs requires an efficient graph partitioner that produces balanced partitions with fewer cut edges/vertices in a reasonable amount of time. Despite several algorithms that have been proposed, it is still insufficient. Even with the continuous growth of graph volume, they do not consider the graph volume during graph partitioning. Therefore, these algorithms generate an imbalanced workload. We propose a graph partitioner algorithm VSCT based essentially on four key metrics: Volume, Size, Cuts, and Time to maintain high-quality graph partitioning. Using real-world datasets, we show that VSCT performs an efficient partitioning quality against the existing graph partitioning algorithms.